2019
DOI: 10.4000/configuracoes.7116
|View full text |Cite
|
Sign up to set email alerts
|

Saúde Mental de Crianças e Adolescentes Portugueses em Acolhimento Residencial

Abstract: Resumo Em Portugal existem mais de 8000 crianças em Acolhimento Residencial (AR). Neste estudo participaram 77 crianças em AR (63,6% rapazes). Através da Bateria ASEBA foi possível observar que os participantes apresentaram níveis clínicos de problemas de saúde mental (maioritariamente as raparigas). Estes estão relacionados com o motivo de acolhimento e com o tipo de apoio recebido. A dimensão da casa medeia a relação entre a sintomatologia e o número de apoios recebidos. Estes resultados apelam à necessidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Esses dados tornam-se ainda mais expressivos quando se comparam os adolescentes institucionalizados com os que possuem convivência familiar. As vivências antes do acolhimento com negligência, violência e maus-tratos, como também a própria institucionalização e separação das figuras de apego, tornam-se preditores de adoecimento mental (Calcing & Benetti, 2014;Campos, Barbosa-Ducharne, Dias & Rodrigues, 2019;WHO, 2021).…”
Section: Resultsunclassified
“…Esses dados tornam-se ainda mais expressivos quando se comparam os adolescentes institucionalizados com os que possuem convivência familiar. As vivências antes do acolhimento com negligência, violência e maus-tratos, como também a própria institucionalização e separação das figuras de apego, tornam-se preditores de adoecimento mental (Calcing & Benetti, 2014;Campos, Barbosa-Ducharne, Dias & Rodrigues, 2019;WHO, 2021).…”
Section: Resultsunclassified
“…Children in residential care have a higher incidence of psychological problems and maladaptive behavior (Campos et al, 2019) when compared to children living with their birth families (Gearing et al, 2015). Accordingly, the impact of punitive and power assertion discipline strategies on children in residential care can be devastating, given their past adversity and trauma experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported that children in residential care show more ambiguous emotions and maladjusted behaviors as a result of past adverse and traumatic experiences related to the absence/discontinuity of affection within their families (Campos et al, 2019;Pace et al, 2019;Seng & Prinz, 2008) when compared to children without any experience of family removal (Gearing et al, 2015). Thus, residential care must guarantee the presence of at least one adult who is genuinely committed to the child, establishing affective bonds that provide support in difficult moments (Carlos et al, 2013).…”
Section: )mentioning
confidence: 99%